Risk Management of Insurance Companies With The Implementation Of The Munich Chain Ladder Method In Claim Reserve Estimation - Rachim Chan (Green Publisher Indonesia, 2024)
Reserve management is a crucial component in corporate risk management. Claims provision refers to funds allocated by the Company to cover claims that may arise from either Incurred But Not Reported (IBNR) or Reported But Not Settled business activities of the Company. (RBNS). There are several different methods commonly used in carrying out the calculation of company claims reserves and one of them is the method munich chain ladder which is the development of chain ladders method. The aim of the study is to apply the munich chain ladder method in calculating the reservation of motor vehicle insurance claims using the motor vehicle insurance claims data from the insurance company PT ABC during the period 2011-2023. The results of the research showed that the method of munich chain ladder can be used to generate more accurate reservation projections of motor vehicles insurance claim compared to the chain ladders method. This study has made an important contribution to the insurance industry in improving the accuracy of the calculation of reservation claims for motor vehicles. By using the munich chain ladder method, insurance companies can make more accurate projections to control risk and manage finances more effectively.